A simplified method to account for vertical human-structure interaction. (August 2021) - Van Nimmen, K.; Pavic, A.; Van den Broeck, P.
Abstract: To account for vertical human-structure interaction (HSI) in the vibration serviceability analysis, the contact force between the pedestrian and the structure can be modelled as the superposition of the force induced by the pedestrian on a rigid surface and the force resulting from the mechanical interaction between the structure and the human body. For the case of large crowds, this approach leads to (time-variant) models with a very high number of degrees of freedom (DOFs). To simplify analysis, this paper investigates the performance of an equivalent single-degree-of-freedom approach whereby the effect of HSI is translated into an effective natural frequency and modal damping ratio for each mode of the supporting structure. First, the numerical study considers a footbridge structure that is modelled as a simply-supported beam for which only the fundamental vertical bending mode is taken into account. For a relevant range of structure and crowd parameters, the comparison is made between the structural response predicted by the simplified model and the more accurate reference model that accounts for all DOFs of the coupled crowd-structure model. Where the simplified model is found to underestimate the structural response, although to a limited extent, this is compensated for by introducing a correction factor for the effective damping ratio. Second, the performance of the simplified method is evaluated through the application on a real footbridge. The results show that the simplified method allows for a good and mildly conservative estimate of the structural acceleration response that is within 10–20% of the predictions of the reference crowd-structure model.